Female genital mutilation in Africa: Scoping the landscape of evidence - Oluchukwu Loveth Obiora; Johanna Elizabeth Maree; Nokuthula Nkosi-Mafutha (Elsevier, 2020)
Background: Despite concerted efforts to curb Female Genital Mutilation/Cutting (FGM/C), it is still a contributor to the high morbidity and mortality rates among females in Africa. Purpose: To describe the publication output on FGM/C conducted in Africa over a period of 10 years and identify trends and gaps to guide future research. Method: A scoping review on FGM/C in Africa was conducted. The keyword 'Africa' in combination with the terms 'female genital mutilation,' 'female genital cutting' and 'female circumcision,' were used to search the databases PubMed, CINAHL, Web of Science and Scopus. Reference lists of tracked articles were used to track other relevant articles. Only peer-reviewed works published between 1 January 2007 and 31 December 2016 were included. The data were captured onto an extraction sheet, while content analysis was used to categorize the findings of the studies and group the categories into themes. Results: Of the 401 articles identified for possible inclusion, only 28 articles met the inclusion requirements. Most of the studies (n = 17; 60.7%) were quantitative and focused on prevalence, attitudes, perpetrators, and health consequences of FGM/C. Two themes and six sub-themes arose from the data. The themes were the practice of FGM/C and the attempts to end FGM/C. Conclusions: FGM/C is still widely practiced in Africa and there may have been an increase in early-age FGM/C in some communities. Studies investigating the experiences of all the role players involved in this practice and how to prevent it were absent. Understanding these phenomena could guide efforts to curb this harmful practice.